Random Propagation through the Longwave Channel - Kelly, F. J.; Rhoads, F. J. (1987)
The longwave propagation channel in the earth ionosphere waveguide has many characteristics of a random medium. The lower surface of the waveguide is sometimes rough or smooth depending on the propagation path considered. The ionospheric boundary is significantly perturbed by sudden events during both daytime and nighttime. The polar-arctic regions of the world evidence these effects in a striking manner and require different statistical treatment. Recent observation of longwave fields in the arctic will be described and their degree of agreement with statistical predictions displayed. (Author) This article is from 'Conference Proceedings of Scattering and Propagation in Random Media Held in Rome, Italy on 18-22 May 1987,' AD-A194 694, p27-1 thru 27-27.